COMPARATIVE STUDY BETWEEN AUTO TAKAFUL AND AUTO INSURANCE PURCHASING BEHAVIOUR AMONG MALAYSIAN UNDERGRADUATES - Ab Rahman, Asmak (Jurnal Syariah, 2008)
In 1984, the Malaysian insurance industry was liberalized to allow for the introduction of Islamically accepted insurance products known as takaful. Among the popular products was the Islamic auto insurance more commonly known as Islamic auto takaful. Given a choice of conventional and Islamic auto insurance the paper attempts to look at the purchasing behaviour of Malaysian undergraduates including the choice of takaful/insurance operator and the purchasing decision-maker. To understand their choices, their perception towards the determinants of selection is also investigated. Undergraduates are chosen because the size and wealth of their market provides excellent opportunities for takaful companies. Based on a survey of 537 respondents in a local university, we found that parents were primarily responsible for the premium payment and, among those who pay themselves, the majority chose conventional auto insurance. Overall, the undergraduates are of the opinion that auto insurance is better than auto takaful in all factors that influence selection – services delivery, services provision, reputation, electronic services and convenience. But, when religiosity was factored in, the Muslim undergraduates ranked it as the top item that makes a difference between auto takaful and insurance, thus showing their possible shift to takaful in the future. Furthermore, this study also shows that there is a tendency among the students to choose auto takaful for their next renewal.